Transient Resistive Switching Memory of CsPbBr3 Thin Films. (12th March 2018) - Lin, Qiqi; Hu, Wei; Zang, Zhigang; Zhou, Miao; Du, Juan; Wang, Ming; Han, Shuai; Tang, Xiaosheng
Abstract: Recently, transient electronic devices play an indispensable role in modern disposable electronics and create potential application fields that cannot be addressed with conventional electronic devices or systems. However, the choice of transient materials has some limitations. It is therefore of great significance to explore transient electrodes, materials, and substrates that can undergo rapid and complete degradation on demand. In this work, the CsPbBr3 thin films as the switching layer are utilized to implement transient memory devices with a flexible Ag/CsPbBr3 /PEDOT:PSS/ITO structure. This flexible nonvolatile memory device exhibits reproducible resistive switching performance, uniform switching voltages, concentrated distributions of high and low resistance states, and good mechanical stability over 50 bending times. The elemental mapping images of the memory device reveal that the resistive switching mechanism is interpreted through electrochemical formation/dissolution of metallic Ag filaments in CsPbBr3 layer. More importantly, it is demonstrated that the CsPbBr3 films and memory device can be dissolved rapidly in deionized water within 60 s, showing the transient characteristics. In addition, the optical and electrical properties disappear completely after the device dissolved in deionized water. This work demonstrates that the all‐inorganic perovskite CsPbBr3 ‐based transient memory devices have great potential for applications in secure data storage systems and disposable electronics. Abstract : A flexible transient nonvolatile memory device made of all‐inorganic perovskite CsPbBr3 is reported by material synthesis, characterization, optical, and electrical measurements. It is found that this device exhibits reproducible resistive switching performance, good mechanical stability, and rapid dissolution time, which has great potential for future applications in secure data storage systems and disposable electronics.